STRATEGY OF EFFECTIVE MANAGEMENT FOR SMALL BUSINESSES AT DIFFERENT STAGES OF INNOVATION ACTIVITY - Riapukhina, Viktoriia N.; Suprun, Emiliya Viktorovna; Doroshenko, Yuri Anatolievich; Bukhonova, Sophia Miroslavovna; Somina, Irina Vladimirovna (Journal of Applied Engineering Science, 2015)
Proven by international experience appropriateness of the model of multiple innovation sources determines the urgency of the problem of development of small enterprises innovative activity. This paper examines the theoretical basis for attribution of "innovation activity" concept i.e. definition, types and stages of innovation, as well as analyzes the methodological aspects of effective management of the small business innovation. This study describes the main negative factors of innovation environment for small business and modern innovation strategies. The authors draw conclusions about effectiveness of application of innovative management strategies at different innovation stages and offer some measures to develop innovative intra-firm behavior.
Keywords: An inter-firm behavior; Innovation strategy; Innovation management; Small business; Innovation stages; Innovation process; Innovative activity